2011
DOI: 10.1152/ajprenal.00640.2010
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral nephrectomy causes an abrupt increase in inflammatory mediators and a simultaneous decrease in plasma ADMA: a study in living kidney donors

Abstract: Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthases (NOS). Reducing inducible NOS activity in acute inflammation seems to be desirable. In vitro data show that ADMA increases in response to inflammatory mediators, yet the effect of acute inflammation in vivo is scarcely studied. The aim of the study was to evaluate ADMA plasma levels before, during, and after the acute (nonbacterial) inflammatory-like state. Plasma ADMA, l-arginine, C-reactive protein, and IL-6 were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“…Additionally, IL-6 has been shown to induce a delayed expression of MCP-1 that mediates the transition from an innate immune response characterized by neutrophil infiltration to an acquired immune response with increased macrophage infiltration (23,44,52). In this study, we demonstrated that IL-6 rapidly increased after nephrectomy, with a delayed increase in MCP-1 at 24 h. Our findings correlate with recently published clinical research showing increased IL-6 levels after laparoscopic donor nephrectomy (26). However, because the objective of Kielstein et al (26) was to evaluate the relationship between asymmetric dimethylarginine and inflammation, no control group was enrolled.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, IL-6 has been shown to induce a delayed expression of MCP-1 that mediates the transition from an innate immune response characterized by neutrophil infiltration to an acquired immune response with increased macrophage infiltration (23,44,52). In this study, we demonstrated that IL-6 rapidly increased after nephrectomy, with a delayed increase in MCP-1 at 24 h. Our findings correlate with recently published clinical research showing increased IL-6 levels after laparoscopic donor nephrectomy (26). However, because the objective of Kielstein et al (26) was to evaluate the relationship between asymmetric dimethylarginine and inflammation, no control group was enrolled.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we demonstrated that IL-6 rapidly increased after nephrectomy, with a delayed increase in MCP-1 at 24 h. Our findings correlate with recently published clinical research showing increased IL-6 levels after laparoscopic donor nephrectomy (26). However, because the objective of Kielstein et al (26) was to evaluate the relationship between asymmetric dimethylarginine and inflammation, no control group was enrolled. Hence, it was not possible to determine whether IL-6 elevation after donor nephrectomy is distinct from other types of intraperitoneal laparoscopic surgery that typically occur from activation of neutrophils, monocytes, and fibroblasts in the surgical field (24).…”
Section: Discussionsupporting
confidence: 87%
“…The concentration of L-arginine was increased in whole-kidney cortex, which probably originated from increased uptake by the proximal tubule due to the increased filtered load. Similar to humans (16), plasma ADMA was slightly increased in early UNX. One explanation for this could be that the kidney is important for ADMA turnover in the body.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to the transgenic mice studies [24,25] in which endothelial DDAH activity controls plasma ADMA, plasma ADMA falls in normal man after acute uninephrectomy for kidney donation [31] and a similar observation was reported in the rat [32] after total nephrectomy. There is no clear mechanism for the fall in plasma ADMA immediately post nephrectomy although the acute inflammatory response to the surgery may be involved [31]. Whatever the explanation it is clear that renal and hepatic DDAH activity are not the only controllers of plasma ADMA.…”
Section: Endogenous Nos Inhibitorsmentioning
confidence: 67%